Do health professionals know about overdiagnosis in screening, and how are they dealing with it? A mixed-methods systematic scoping review - Veerle Piessens; Ann Van den Bruel; An Piessens; Ann Van Hecke; John Brandt Brodersen; Emelien Lauwerier; Florian Stul; An De Sutter; Stefan Heytens (PLoS ONE, 2025)
Introduction Medical screening is a major driver of overdiagnosis, which should be considered when making an informed screening decision. Health professionals (HPs) often initiate screening and are therefore responsible for informing eligible screening participants about the benefits and harms of screening. However, little is known about HPs’ knowledge of overdiagnosis and whether they are prepared to inform screening candidates about this risk and enable people to make an informed screening decision. Methods This is a systematic review of studies examining HPs’ knowledge and perception of overdiagnosis, whether it affects their position on offering screening, and their willingness to inform screening candidates about overdiagnosis. We conducted systematic searches in MEDLINE, Embase, Web of Science, Scopus, CINAHL, and PsycArticles without language restrictions. Two authors analysed the qualitative and quantitative data separately. Confidence in the findings of the qualitative data was assessed using the GRADE-CERQual approach. Results We included 23 publications after screening 9786 records. No studies directly examined HPs’ knowledge of overdiagnosis. HPs’ perceptions of overdiagnosis varied widely, from considering it a significant harm to seeing it as negligible. This seems linked to their overall beliefs about the benefits and harms of screening and to their position on offering screening, which varies from discouraging to actively promoting it. HPs also hold diverging approaches to informing screening candidates about overdiagnosis, from providing detailed explanations to limited or no information. Conclusion There is a lack of research on HPs’ knowledge of overdiagnosis, however, HPs who do know about overdiagnosis attribute substantially different levels of harm to it. This seems intertwined with their overall beliefs about the benefits of screening, their position towards offering screening, and their willingness to inform screening candidates about overdiagnosis. This has important implications for the public’s right to evidence-based information and compromises an individual’s right to make an informed screening decision.